The waters and the wild : an Underhill adventure - Lackey, Mercedes; Edghill, Rosemary (Bedlam's bard, 2019)
"Deeply depressed Olivia, whose parents are divorcing, is ripe for manipulation. And swimming star Blake is looking for someone just like her. Although her friend tries to warn her, Olivia falls for his ploys and accepts an invitation to go to the Adirondack resort camp of Lake Endor with him and his family. But all is not as it seems at the hundred year old resort. Not only does Olivia discover that Blake is not the guy she thought he was, there is something sinister afoot at the lake. There is something lying beneath the waters of Lake Endor. Something not of this world. Will Olivia be drawn under or will she allow true friends to draw her from the lure of oblivion?"--